Sosialisasi Manfaat Inisiasi Menyusui Dini (IMD) Sebagai Langkah Awal Mensukseskan Program ASI Eksklusif di Kota Padang - Asyari, Dian Paramitha; Hasnah, Fadhilatul (Universitas Alifah Padang, 2024)
Abstract The low rate of exclusive breastfeeding indicates the failure of the nation to prepare quality human resources. The success of the IMD program is strongly influenced by several factors, one of which is socialization. Socialization is a way of conveying information to the public and can influence their knowledge and understanding of something. Lack of knowledge from parents, and medical authorities, and reluctance to do so makes IMD still rarely practised. The implementation of IMD is a new thing in Indonesia, especially in several hospitals in Padang City, both government and private hospitals. Information about the IMD process is very influential in shaping the intention of mothers who will soon give birth to want to apply the IMD process after childbirth. Health facilities such as hospitals should help new mothers to perform IMD. Therefore, researchers are interested in examining the implementation of socialization about the benefits of IMD in Padang City.